Penetapan Kadar Klorofil dan Karotenoid Daun Sawi (Brassica) Menggunakan Metode Spektrofotometri UV-Vis - Eni Kartika Sari (Jurnal Kimia Fullerene, 2020)
Chlorophyll and carotenoids are antioxidant compounds that are very potential. Both of these compounds are found in many vegetables. This research aims to determine the levels of chlorophyll and carotenoids in mustard (Brassica) leaves. There were three types of mustard leaves tested, namely greens mustard (Brassica rapa I.), white mustard (Brassica juncea L.) and pakcoy (Brassica rapa L.). Analysis of samples by the Uv-Vis Spectrophotometry method. The results of the measurement of chlorophyll levels showed that pakcoy (Brassica rapa L.) had the highest chlorophyll level which was 86,76 mg/g. While the lowest chlorophyll level is found in the type of white mustard which is equal to 0,75 mg/g. From the three of the mustard tested, green mustard (Brassica rapa I.) and pakcoy (Brassica rapa L.) were mustard types that contained high carotenoids in the amount of 50,4 mg/g and 198,04 mg/g. While the type of white mustard (Brassica juncea L.) has the lowest carotenoid content for all preparations.